Implementasi Metode Game-Based Learning Berbantuan Aplikasi Quizizz - Pamela, Ananda Bintang; Usmeldi, Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
This study aims to determine the learning outcomes of students after the implementation of the game-based learning method assisted by the Quizizz application in the Basic Electricity Engineering subject at SMK Negeri 1 Rejang Lebong. In an effort to improve student learning outcomes, interesting and interactive learning media are needed. This study used an experimental approach with a pre-experimental method, as well as a one group pretest-posttest design. The research instruments used were pretest and posttest questions in objective form to assess student learning outcomes. Before use, the instrument was tested with validity test, reliability test, differentiator test, and question difficulty index to ensure the feasibility of the tools used. The results indicated an increase in the learning outcomes of students who applied the game-based learning method assisted by the Quizizz application, when compared to conventional learning methods. Nevertheless, this study also has some limitations, such as the focus on only one school and one subject. Therefore, further research involving more schools and subjects is expected to provide a more comprehensive picture of the application of this method. In addition, the factors of student motivation and previous experience in the same subject also need to be considered in future research. This research provides a strong foundation for curriculum development and learning approaches to improve students' understanding of electricity fundamentals.